Laparoscopic excision of deep rectovaginal endometriosis in BSGE endometriosis centres: a multicentre prospective cohort study - Paul Smith; Lucky Saraswat; Sanjay Vyas; Thomas Ind; Ertan Saridogan; Elizabeth Ball; Edward Morris; James Clark; Tony Chalhoub; David Rowlands; Moiad Alazzam; Dominic Byrne; et al. (BMJ Open)
Objective To estimate the effectiveness and safety of laparoscopic surgical excision of rectovaginal endometriosis.Design A multicentre, prospective cohort study.Setting 51 hospitals accredited as specialist endometriosis centres.Participants 5162 women of reproductive age with rectovaginal endometriosis of which 4721 women had planned laparoscopic excision.Interventions Laparoscopic surgical excision of rectovaginal endometriosis requiring dissection of the pararectal space.Main outcome measures Standardised symptom questionnaires enquiring about chronic pelvic pain, bladder and bowel symptoms, analgesia use and quality of life (EuroQol) completed prior to surgery and at 6, 12 and 24 months postoperatively. Serious perioperative and postoperative complications including major haemorrhage, infection and visceral injury were recorded.Results At 6 months postsurgery, there were significant reductions in premenstrual, menstrual and non-cyclical pelvic pain, deep dyspareunia, dyschezia, low back pain and bladder pain. In addition, there were significant reductions in voiding difficulty, bowel frequency, urgency, incomplete emptying, constipation and passing blood. These reductions were maintained at 2 years, with the exception of voiding difficulty. Global quality of life significantly improved from a median pretreatment score of 55/100 to 80/100 at 6 months. There was a significant improvement in quality of life in all measured domains and in quality-adjusted life years. These improvements were sustained at 2 years. All analgesia use was reduced and, in particular, opiate use fell from 28.1% prior to surgery to 16.1% at 6 months. The overall incidence of complications was 6.8% (321/4721). Gastrointestinal complications (enterotomy, anastomotic leak or fistula) occurred in 52 (1.1%) operations and of the urinary tract (ureteric/bladder injury or leak) in 49 (1.0%) procedures.Conclusion Laparoscopic surgical excision of rectovaginal endometriosis appears to be effective in treating pelvic pain and bowel symptoms and improving health-related quality of life and has a low rate of major complications when performed in specialist centres.